Cancer incidence, trends, and survival among immigrants to Sweden: a population-based study. (March 2015) - Mousavi, Seyed Mohsen; Hemminki, Kari
Abstract : This review aimed at covering cancer risk trends by site and histology in first-generation and second-generation immigrants in Sweden compared with natives. In addition, we reviewed data on cancer survival in immigrants to explore factors explaining cancer survival in the entire population. The Swedish Family-Cancer Database was used to calculate standardized incidence ratios and hazard ratios (HRs) of death from cancer in 77 360 and 993 824 cases among first-generation, and 4356 and 263 485 cases among second-generation immigrants and Swedes, respectively. Ordinal logistic regression analyses were used to calculate odds ratio. To obtain the maximum number of cases, we classified the immigrants according to geographical setting, population, and/or cancer risk. Compared with native Swedes, the highest risk of cancer was observed for nasopharyngeal carcinoma in Southeast Asian men (standardized incidence ratio=35.6) and women (24.6), for hypopharyngeal carcinoma in Indian men (5.4), for squamous-cell carcinoma of the esophagus in Iranian women (3.8), for cardia of the stomach in East Asian women (4.2), for signet-ring cell carcinoma of the stomach in Southeast Asian women (6.7), for the liver in East Asian men (6.8), for the gall bladder in Indian women (3.8), for the pancreas in North African men (2.2), for large cell carcinoma of the lung in former Yugoslavian men (4.2), for pleural mesothelioma in Turkish women (23.8), for the cervix in Danes (1.6), for seminoma in Chileans (2.1), for transitional-cell carcinoma of the bladder in Asian Arab men (2.3), for meningioma in former Yugoslavians (1.3), and for papillary carcinoma of the thyroid in East and Southeast Asian men (3.6). No immigrant groups had an increased risk of breast, uterus, ovary, and prostate cancers or nervous system tumors. The HRs for all breast cancers were between 1.0 in low-risk Europeans and 1.2 in lowest-risk non-Europeans. Low-risk non-Europeans had an HR of 2.9 for lobular carcinoma. Low-risk non-Europeans were diagnosed in a higher T-class (odds ratio=1.9) than Swedes. The HRs for prostate cancer were 0.6 in Turks, Middle Easterners, Asians, and Chileans. In conclusion, environmental and behavioral factors, early-childhood exposures, and infections may play a major role in the risk of esophageal, stomach, liver, nasopharyngeal and hypopharyngeal cancers, malignant pleural mesothelioma, breast, gynecological, testicular, urinary bladder, and thyroid cancers. Pancreatic cancer and nervous system tumors may have a major genetic component in the etiology. The ethnic differences in the risk of breast cancer by histology had no major influence on survival. Middle Easterners, Asians, and Chileans, with the lowest risk of prostate cancer, also had the most favorable survival, suggesting a biological mechanism for this finding.